Typology and correlates of political participation among Filipinos. [article]. - Sucgang, Evangeline P.
The study sought to establish the types of political participation among Filipino citizens including some of its attitudinal and social structural-demographic correlates. Using data from 2001 national survey on Filipino citizenship, 17 political participation items were subjected to an exploratory factor analysis. Two types of political involvement surfaced namely, political participation as proactive engagement in the public arena and political participation as public problem solving. Multiple regression analysis to determine possible correlates revealed the presence of two-way interaction effects for both types of political engagement. Data gathered from interviews with 20 respondents yielded 11 other forms of participation that are reflective of the evolving nature of political engagement as it is influenced by the Philippine socio-cultural and political history. A research agenda for future work on this area is also proposed. -- (from the author)